The mauve stinger Pelagia noctiluca (Cnidaria, Scyphozoa) plastics contamination, the Strait of Messina case. Issue 6 (2nd November 2021) - Albano, Marco; Panarello, Giuseppe; Di Paola, Davide; D'Angelo, Giovanna; Granata, Antonia; Savoca, Serena; Capillo, Gioele
ABSTRACT: It is well known that microplastics are ingested by a wide range of marine organisms. Little is known about their occurrence in cnidarians. The paper reports microplastic contamination in Pelagia noctiluca, collected from the Strait of Messina. Our results confirm the ability of this species to uptake plastic particles, in relation to its feeding behaviour.